Philanthropic Traditions in Religions; A Comparative Study of Jews, Islam, and Christianity - Sobiyanto, Ahmad; Nurwahidin, Nurwahidin (UI Scholars Hub, 2023)
The philanthropic tradition is one of the recommended acts of worship in Islam which is part of the pillar of Islam, zakat. However, it turns out that this tradition also developed in other religions and became interesting to learn. The purpose of this study is to describe qualitatively about philanthropic traditions in the teachings of major religions in the middle east, namely Judaism, Islam, and Christianity. Descriptive qualitative method (using content analysis techniques) is a type of literature research through books, journals and other relevant sources used in this research. That the religions of Judaism, Islam, and Christianity each have concepts and practices regarding philanthropy as a result of this research. Jews have a concept of charity that is practiced with Tzedakah activities for the poor. Islamic teachings have a philanthropic concept in the form of Islamic zakat pillars which are also practiced in the form of zakat, Infaq / alms, and Waqf. Christianity has a philanthropic concept in the form of compassion for the poor which is practiced by giving tithes and year-end offerings.